The Role of Cultural Festivals in Fostering Social Cohesion in Multicultural Societies in Brazil - Oliveirra, Sandro Louise (Enigma Institute, 2024)
Cultural festivals serve as vital platforms for celebrating diversity and promoting social cohesion in multicultural societies. This study investigates the role of cultural festivals in fostering social cohesion within the context of Brazil, a nation known for its rich cultural tapestry and diverse population. A mixed-methods approach was employed, incorporating qualitative and quantitative data collection techniques. In-depth interviews were conducted with festival organizers, participants, and community members to gain insights into their experiences and perceptions. Additionally, surveys were administered to assess the impact of festivals on social cohesion, measuring factors such as intergroup contact, trust, and shared identity. The findings revealed that cultural festivals play a significant role in fostering social cohesion in Brazil. Festivals provide opportunities for individuals from different cultural backgrounds to interact, exchange ideas, and celebrate their shared humanity. Participation in festivals was associated with increased intergroup contact, enhanced trust, and a stronger sense of shared identity. In conclusion, this study underscores the importance of cultural festivals as catalysts for social cohesion in multicultural societies. Festivals create spaces for intercultural dialogue, promote understanding, and foster a sense of belonging among diverse communities. The findings have implications for policymakers, community organizers, and researchers interested in leveraging cultural festivals to build more inclusive and cohesive societies.